Analisis Keharmonisan Antara Agama Hindu Dan Buddha Pada Candi Jawi - Adhitama, Satria (Jurnal Penelitian Agama Hindu, 2023)
The phenomenon of intolerance and conflict with religious nuances is currently commonly found in the lives of Indonesian people. Even though the temples describe the life of the Archipelago in harmony between adherents of religions, one of which is the Jawi Temple. This research aims to dig deeper into the harmony between the Shiva religion (Hindu) and Buddhism in Jawi Temple. A qualitative descriptive approach is an approach used with a constructionist strategy that describes in detail about Jawi Temple which is a symbol of harmonization of Hinduism and Buddhism. Data collected by interview, observation, and documentation. The selection of informants or research subjects was carried out purposively. Evidence that Jawi Temple is a symbol of harmony between Hinduism and Buddhism is that in Jawi Temple there are statues of Hinduism, namely the statues of the God Tri Murti (Brahma, Vishnu, Shiva), Lord Ganesha, Goddess Durga, Ardhanari, and Kalki. Besides that, there are mythological animals from Hinduism, namely Kala and Makara. Buddhism is represented by a stupa at the top of the temple and there was once an Aksobhya  statue in Jawi Temple. The relief on Jawi Temple tells of Prince Sutasoma who is proposing to Princess Candrawati. Prince Sutasoma is a prince from the Astina Kingdom of India who is Buddhist but respects Hinduism very much. In the reliefs of Jawi Temple there are also images of Shiva (Hindu) and Buddhist people living peacefully and peacefully while studying together. So, the value that can be taken from Jawi Temple is the strong value of tolerance between Shiva (Hindu) and Buddhist religions. The implication of this research is to strengthen the spirit of tolerance for diversity in Indonesia and one of the factors that determines tolerance in a society is the policies adopted by moderat leaders.